2003
DOI: 10.1177/014107680309600707
|View full text |Cite
|
Sign up to set email alerts
|

Public Views on Healthcare Performance Indicators and Patient Choice

Abstract: Patients on certain waiting lists in the UK National Health Service (NHS) are now offered the choice of persevering with their home hospital or switching to another hospital where they will be treated on a guaranteed date. Such decisions require knowledge of performance. We used facilitated focus groups to investigate the views of patients and members of the public on publication of information about the performance of healthcare providers. Six groups with a total of 50 participants met in six different locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 11 publications
0
30
0
4
Order By: Relevance
“…Despite its prevalence, performance data is rarely used by patients in the United States and United Kingdom, who claim to prefer anecdotal reports from family and friends [15][16][17]. Performance data tends to focus on biomedical outcomes of treatment such as survival, but studies focused on primary, nursing and acute care found that patients are more interested in knowing about the quality of interpersonal interactions with health care providers [18][19][20].…”
Section: Patient Involvement In Service Evaluationmentioning
confidence: 99%
“…Despite its prevalence, performance data is rarely used by patients in the United States and United Kingdom, who claim to prefer anecdotal reports from family and friends [15][16][17]. Performance data tends to focus on biomedical outcomes of treatment such as survival, but studies focused on primary, nursing and acute care found that patients are more interested in knowing about the quality of interpersonal interactions with health care providers [18][19][20].…”
Section: Patient Involvement In Service Evaluationmentioning
confidence: 99%
“…It is therefore highly important to inform these professionals on the characteristics of hospitals [21]. When undertaking an advisory role, the GP should be able to distinguish their personal opinions from objective information [22,23].…”
Section: Resultsmentioning
confidence: 99%
“…It would dramatically change the position of the health care professions, whose position I shall discuss further below. And although I have argued that this kind of choice follows a cultural trend in western society, as Magee et al [33] point out, it is far from clear that patients actually want choice on this scale at present, or feel able to exercise it. Despite being culturally resourced (as I have suggested) to formulate a wide range of preferences, people seem to be held back by the lack of other necessary resources, such as information, confidence [41] or the skill to use information appropriately [29].…”
Section: Introductionmentioning
confidence: 92%